Race to the debt trap? Spatial econometric evidence on debt in German municipalities - Frank M. Fossen; Ronny Freier; Thorsten Martin (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
Through an intertemporal budget constraint, jurisdictions may gain advantages in tax and spending competition by 'competing' on debt. While the existing spatial econometric literature focuses on tax and spending competition, very little is known about spatial interaction via public debt. This paper estimates the spatial interdependence of public debt among German municipalities using a panel on municipalities in the two largest German states from 1999 to 2006. We find significant and robust interaction effects between debt of neighboring municipalities, which we compare to spatial tax and spending interactions. The results indicate that a municipality increases its per capita debt by 16-33 Euro as a reaction to an increase of 100 Euro in neighboring municipalities.
Keywords: C23; H63; H74; R12; 330; public debt; tax and spending competition; municipality data; spatial interactions; spatial panel estimation